Correlation of Height and Maximum Overhead Reach Among Adult Individuals (Journal of Forensic Medicine & Toxicology, 2025)
To analyze the correlation between height and maximum overhead reach among individuals having a height between 150-182 cm. This cross-sectional observational study was conducted on 320 cases with an equal \ proportion of both sexes i.e.,160 males as well as 160 females in the Forensic Medicine Department, UCMS & Guru Teg Bahadur Hospital. A formula for linear regression was devised to calculate an individual’s maximal overhead reach from standing height. This formula was tested on a sample of living and deceased individuals from the population of North India aged 21-30 years. In addition to helping to rule out any foul play, this overhead reach estimate will be helpful in determining if the apparent suicide victim had been capable of reaching the point of suspension
Keywords: Height; Overhead Reach; Cadaver; Forensic